Peran Brand Equity terhadap Pengaruh Kualitas Pelayanan dan Loyalitas Pasien pada Suatu Rumah Sakit - Leo, Jeanette Rachel Audrey; Lina , Lina (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the role of brand equity in strengthening the influence of service quality on patient loyalty in a hospital located in Lampung Province, Indonesia. The brand equity in this research includes five elements: brand awareness, brand image, perceived quality, brand association, and brand loyalty. A quantitative approach with a cross-sectional design was employed. The sampling technique used was purposive sampling, and data were collected through a five-point Likert scale questionnaire distributed to hospital patients. Data were analyzed using descriptive and inferential statistical methods through correlation and regression testing. The results indicate that service quality has a positive effect on patient loyalty, and brand equity not only has a direct impact on loyalty but also moderates the relationship between service quality and loyalty. These findings highlight the importance of managing brand equity as part of health service strategies to enhance patient satisfaction and retention amid increasing competition among hospitals.